Canon, criterion and circularity: An analysis of the epistemology of canonical theism - Morris-Chapman, Daniel J. Pratt (HTS teologiese studies, 2018)
In recent years, William J. Abraham has suggested the creation of a new subdiscipline for examining the epistemology of theology. This article provides an overview of this proposal, highlighting some of the philosophical concepts, such as ‘Aristotelian epistemic fit’ and particularism, that Abraham drew upon when formulating this approach. It then proceeds to an examination of Abraham’s application of these ideas to his preferred theological scheme, canonical theism. Limitations and challenges to Abraham’s position are discussed as well as ways in which weaknesses in his approach might be addressed.